INCIDENCE OF BENIGN PROSTATIC HYPERPLASIA IN DOGS - DHIVYA, T R; SRIDEVl, P; KULASEKAR, K; KUMARASAMY, P (The Indian Journal of Animal Reproduction, 2023)
The data obtained for 604 dogs from clinical records (July 2008-August 2009) and screening of 216 clinical cases brought to Madras Veterinary College during the study period (September 2009 to May 20.10) were pooled to study the incidence of prostatic affections, age and breed related incidence of Benign Prostatic Hyperplasia (BPH) among dogs.